Effectiveness of Home-Based Stretching and Strengthening Training for Improving Flexibility, Strength, and Physical Function in Older Adults with Leg Tightness and/or Suspected Sarcopenia - Pornpimol Muanjai; Sirawee Chaovalit; Nongnuch Luangpon; Wirasinee Srijunto; Pongrung Chancharoen; Juntip Namsawang; Piyapong Prasertsri; Sigitas Kamandulis; Tomas Venckunas; Orachorn Boonla (Sports)
Background/Objectives: The aim of the present study was to assess the effectiveness of flexibility or strengthening exercises to improve flexibility, strength, muscle architecture, and functional performance in older adults with leg tightness and/or suspected sarcopenia. Methods: Ninety adults with leg tightness and/or suspected sarcopenia (age: 66.8 ± 4.9 years) were randomly allocated to two subtypes of intervention at home: resistance-band exercise (RE) or eccentric exercise (ECC) for those with weakness; static or dynamic stretching for those with tightness; and static stretching plus ECC or no exercise for those with both muscle tightness and weakness. The program consisted of 3–6 weekly sessions over eight weeks. Blinded outcome assessments before and after the eight-week program and at the three-month follow-up included mobility performance via Timed Up-and-Go (TUG), and flexibility and strength tests, as well as measurement of stiffness. Results: All groups had increased peak torque after eight weeks and improved TUG at the three-month follow-up (p < 0.05). Improved plantar flexor strength persisted at the three-month follow-up (p = 0.009). In addition, the RE and ECC groups had increased muscle thickness by 4.0 and 8.7% after eight weeks (p < 0.05). Hamstring flexibility increased in all exercise groups, except the RE group. Moreover, all six groups showed improved calf flexibility, whereas no changes in stiffness were noted. Conclusions: Increases in mobility performance, strength, and flexibility appeared due to learning effects and increased physical activity, rather than the specific training impact. However, strength-based programs may be recommended for older adults with suspected sarcopenia, as they provide additional benefits, such as short-lasting muscle hypertrophy.